Developing a cash budget for the Savannah Squares - Barnhill, Christopher R.; Rundio, Amy (London : Human Kinetics, Inc., 2021)
This case challenges students to create a cash budget for a minor league baseball club. Like many sport organizations, minor league clubs are seasonal businesses, meaning they have irregular cash inflows and outflows. Cash management, that is, the ability to manage monthly cash inflows and outflows, is particularly important for seasonal businesses to identify potential shortfalls and plan accordingly. Placed in the role of team president for the Savannah Squares, students will be challenged to break down the club's pro-forma budget into monthly revenue and expense budgets using information contained within the case. Following a suggested cash management strategy, students will use their monthly revenue and expense budgets to create a cash budget for the club.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cash management -- Case studies; Cash budgets -- Case studies